EFFECT OF WATER CURING TEMPERATURE ON COMPRESSIVE STRENGTH DEVELOPMENT AND WATER ABSORPTION CAPACITY OF MORTAR MIXTURES - Mardani Aghabaglou, Ali; Özen, Süleyman; Altun, Muhammet Gokhan; Faqiri, Zia Ahmad (Yildiz Technical Univ, 2020)
In this study, the effect of different curing temperature processes on the 1, 3, 7 and 28-day compressive strength and 28-day water absorption ratios of mortar mixtures were investigated. All mortar mixtures were prepared according to ASTM C109. The water/cement ratio, sand/binder ratio and flow values of mortar mixture were kept constant as 0.485, 2.75 and 25 +/- 2 cm, respectively. Polycarboxylate ether-based high range water reducing admixture was used for providing desired flow value. All mortar mixtures were cured at fresh state in a curing room under the same conditions (Temperature of 20 degrees C and Relative humanity (RH) of 95%) during 24 hours from casting. Then, specimens were subjected to 6 different water-curing conditions. According to test results, the 3-day compressive strength of mixtures cured in water having a temperature of 40 degrees C was higher than that of mixtures cured at 20 degrees C in water. At early ages, the high curing temperature negatively affected the 7 and 28-day compressive strength of mixtures. Specimens cured in water at 20 degrees C and 40 degrees C had the highest and lowest 28-day compressive strengths, respectively. Different curing conditions had no significant effect on the 28-day water absorption ratios of mortar mixtures.
Keywords: Mortar mixture; curing conditions; water absorption; water curing temperature; compressive strength